2024
DOI: 10.1021/acs.inorgchem.3c03906
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Commercially Iron Powder Electron Transport by Surface Biosulfuration to Achieve Uranium Extraction from Uranium Ore Wastewater

Guolin Yang,
Ling Wei,
Xin Wang
et al.

Abstract: The zero-valent iron (ZVI) has attracted increasing attention due to the enhanced reactivity of ZVI to uranium wastewater. However, ZVI practical application is hampered due to its susceptibility to oxidation and the formation of passivation layers during storage and in situ restoration. To address these issues, we used a biosulfuration approach to modify ZVI for application in uranium ore wastewater treatment. A series of physicochemical characterization tools and photoelectronic analyses showed that BS-ZVI c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 54 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…EIS spectra depicted in Figure b illustrate that S 3 -H-ZFO has the least impedance arc radius, implying a decrease in resistance to transport photogenerated electrons. This further demonstrates that moderate S doping enhances electron transport efficiency. , Excessive S doping leads to a decrease in photocurrent response intensity and an increase in impedance value, consistent with the previously observed morphological collapse in SEM images and weakened photocatalytic performance. Furthermore, Figure S9 shows that the fluorescence intensity of S 3 -H-ZFO is significantly weaker than that of H-ZFO, confirming the lower rate of photogenerated electron–hole complexation in the S 3 -H-ZFO photocatalyst, which is consistent with the observations above.…”
Section: Resultsmentioning
confidence: 99%
“…EIS spectra depicted in Figure b illustrate that S 3 -H-ZFO has the least impedance arc radius, implying a decrease in resistance to transport photogenerated electrons. This further demonstrates that moderate S doping enhances electron transport efficiency. , Excessive S doping leads to a decrease in photocurrent response intensity and an increase in impedance value, consistent with the previously observed morphological collapse in SEM images and weakened photocatalytic performance. Furthermore, Figure S9 shows that the fluorescence intensity of S 3 -H-ZFO is significantly weaker than that of H-ZFO, confirming the lower rate of photogenerated electron–hole complexation in the S 3 -H-ZFO photocatalyst, which is consistent with the observations above.…”
Section: Resultsmentioning
confidence: 99%
“…The separation rate and transport rate of photogenerated electron–hole (e – –h + ) pairs generated by metalloporphyrins were evaluated using electrochemical impedance spectroscopy (EIS) and transient photocurrent response (TPR). The former (Figure d) showed that Ni/DAT-porphyrin has the smallest impedance arc radius when compared with Co/DAT-porphyrin and Cu/DAT-porphyrin, indicating that the e – –h + pairs could be separated more effectively in Ni/DAT-porphyrin . The latter (Figure e) demonstrated that the photocurrent of Ni/DAT-porphyrin is higher than those of the other two metalloporphyrins, revealing the higher charge transfer efficiency in Ni/DAT-porphyrin.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, there are many methods for treating the U­(VI) wastewater including reduction of U­(VI) into U­(IV) by photocatalytic , and zerovalent iron, adsorption of U­(VI) by porous materials, and precipitation of U­(VI) into precipitates. Among them, the reduced U­(IV) could be possibly reoxidized into U­(VI), while the adsorbed U­(VI) could be desorbed due to the change in the geochemical conditions. They performed the potential migration and leaching risk .…”
Section: Introductionmentioning
confidence: 99%